Electrical properties of staggered electrode, solution-processed, polycrystalline tetrabenzoporphyrin field-effect transistors - Shea, P.B.; Johnson, A.R.; Ono, N.; Kanicki, J. (IEEE Transactions on Electron Devices, 2005)
We characterize and analyze the electrical performance of solution-processed, polycrystalline tetrabenzoporphyrin thin-film field-effect transistors with staggered source and drain contacts. Devices demonstrated a saturation field-effect mobility and threshold voltage on the order of 10/sup -2/ cm/sup 2//V-s and -15 V, respectively, as well as a subthreshold slope of 1.2 V/decade and an ON-/OFF-current ratio exceeding 10/sup 5/. The device performance and electronic properties of the thin film were used to construct device energy band diagrams. Lastly, the device conduction mechanism is discussed.